The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1180/clm.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotalcites with heterogeneous anion distributions: a first approach to producing new materials to be used as vehicles for the successive delivery of compounds

Abstract: Hydrotalcites with heterogeneous distributions of anions between their layers were synthesized. Some synthesis parameters were studied to verify their influence on the anionic segregation properties of the hydrotalcites. The nature of the divalent cation and the crystallization method were most relevant. Zinc, in contrast to magnesium, assisted in discriminating carbonates and attracting nitrates to form hydrotalcites with heterogeneous distributions using microwave irradiation. Furthermore, the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This difference may be attributed to the presence of mostly interlayered nitrates rather than carbonates in the sample containing zinc, while the sample containing magnesium is richer in carbonates. [14] The peaks appearing at 61-63° (2θ), corresponding to the 110 and 113 reflections, are not well resolved. This could be due by the presence of copper, which introduces serious deformations in the octahedron coordination structure leading to a reduction of crystallinity [15] mostly in presence of magnesium.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…This difference may be attributed to the presence of mostly interlayered nitrates rather than carbonates in the sample containing zinc, while the sample containing magnesium is richer in carbonates. [14] The peaks appearing at 61-63° (2θ), corresponding to the 110 and 113 reflections, are not well resolved. This could be due by the presence of copper, which introduces serious deformations in the octahedron coordination structure leading to a reduction of crystallinity [15] mostly in presence of magnesium.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…37 In order to further prove the presence of anion species in the intercalation of hydrotalcite materials and the structural when Na 2 CO 3 was used as the precipitant during the coprecipitation process, but no NO 3 À decomposition was observed in the calcination process, which showed that CO 3 2À anions were easier to enter the interlayer of hydrotalcite than NO 3 À ions. 35,40 On the other hand, in the samples prepared with mixed alkali as the precipitant, only a small amount of NO 2 was released at near 330 C, indicated that only a trace amount of NO 3 À ions existed in the CuMgAl-Mix and the NO 3 À can be completely decomposed below 330 C. From the mass spectrum signal of CO 2 in Fig. 4C, it can be seen that CO 2 was released in all samples during high-temperature decomposition.…”
Section: àmentioning
confidence: 99%
“…The Coprecipitation technique is the most common method to prepare iron oxide nanoparticles. Both sodium hydroxide (NaOH) and ammonium hydroxide (NH 4 OH) have been used to detect whether the basicity manipulates the crystallization process during particle formation 8,32 . Various surface modification techniques have been used to enhance nanoparticles' diagnosis and therapeutics potential in biomedicine applications 6 .…”
Section: Introductionmentioning
confidence: 99%